Comparative Study of Naugle and Hertel Exophthalmometry in Orbitozygomatic Fracture. Issue 1 (January 2016) - Jeon, Hong Bae; Kang, Dong Hee; Oh, Sang Ah; Gu, Ja Hea
Abstract : Abstract: Accurate perioperative evaluation of enophthalmos is important to determine the adequacy of surgical repair in orbitozygomatic fracture. In this study, the authors evaluated the degree of enophthalmos using Hertel and Naugle exophthalmometry in patients with pure blowout fracture and orbitozygomatic fracture, and compared the results. Fifty patients were divided into 2 groups: pure blowout fracture (Group A: control group, 25 patients) and orbitozygomatic fracture with displaced lateral orbital rim (Group B: experimental group, 25 patients). Hertel and Naugle scales were measured before and 6 months after surgery. The degree of lateral orbital rim advancement was assessed by comparing the difference between the perioperative change of the Hertel and Naugle scales. In Group A, the difference between the pre- and postoperative scales in the 2 exophthalmometry was statistically significant ( P   <  0.05). In Group B, the Hertel scale increased from −0.20 to −0.16 mm, with an insignificant difference between pre- and postoperative values ( P  > 0.05) and the Naugle scale increased from −0.88 to −0.20 mm, with a significant difference ( P   <  0.05). The Δ Hertel scale differed from the Δ Naugle scale by a mean of −0.64 mm, which represents the degree of lateral orbital rim advancement. Naugle exophthalmometry is a more reliable method for evaluation of enophthalmos in lateral orbital rim displaced orbitozygomatic fractures than Hertel exophthalmometry. The degree of lateral orbital rim advancement can be assessed by combined use of the Hertel and Naugle exophthalmometry in orbitozygomatic fractures.